Survival and growth of nursery inoculated Fraxinus uhdei in acrisol gullies - Báez-Pérez, Ana Laura; Lindig-Cisneros, Roberto; Villegas, Javier (Instituto de Ecología, A.C., 2017)
Presence of degraded soils is increasing worldwide, but in many scenarios the knowledge to undertake restoration has not been acquired in an efficient, economical and socially acceptable manner. There are estimates placing moderate to severe degradation of agricultural land worldwide at 80%. Severely degraded substrates, such as gullies, sometimes lack the necessary microbiota for appropriate plant growth, under these conditions nursery inoculation can improve plant performance in the field. In order to explore the role of dual mycorrhization in Fraxinus growing in poor substrates, and also to contribute information on their usefulness in gully restoration, an experiment was conducted in which individuals of this species were inoculated with an endomycorrhyzal fungus, and ectomycorrhizal fungus and with both types of mycorrhizal fungi simultaneously, as well as urea fertilization. The results of this experiment show that establishment of Fraxinus uhdei is possible in severely degraded sites, it also provides information on the effects on the plant of multiple inoculation that cause some performance variables to improve as a result of the interaction, as was the case for the improved survival with the P. tinctorius, G. intraradices dual inoculation; whereas growth variables showed improved response to inoculation with only one of the fungi, height to inoculation with G. intraradices, and cover, number of leaves and diameter at base to inoculation with P. tinctorius. Given the improvements in growth and survival, our results suggest that in severely degraded soils, nursery inoculation of plants adapted to adverse conditions with mycorrhyzal fungi should be implemented.